Analysis of Gender Gap in Women's Leadership: Comprehensive Steps for Effective Implementation and Policy Development - Rochaeni, Siti; Purnomowati, Rahmi; Ichdayati, Lilis Imamah; Rahmadona, Lola (Archives of Business Research, 2025)
This study examines the relationships between various variables that affect the gender gap and women's leadership through structural data analysis using quantitative methods with Smart PLS 3. The model includes latent variables such as Social Roles and Women's Empowerment (X1), External Influences and Policies in Women's Empowerment (X2), Relationship-Based Approaches and Gender Identity (X3), Innovation and Digitalization in Gender Development (X4), as well as Social Roles and Responsibilities in Organizations (X5), all of which are related to Leadership and Gender Equality (Y1). The analysis results show that X2, heavily influenced by the indicators of Gender and Development in the Context of Feminism (X2.1) and the Emiratization Program in the UAE (X2.2), has a substantial impact on X1. Additionally, positive relationships were found between X3 and X2, as well as X3 and Y1, indicating that initiatives that enhance X3, such as Awareness and Social Justice Training in Leadership (X3.2) and Gender Identity Expression in Mainstream Dancesport in the U.S. (X3.3), can significantly contribute to the improvement of X2 and Y1. Although the influence of X4 on Y1 is weaker, there is still a modest positive effect. The strong relationship between X5 and X4 indicates that improvements in X5, mainly through the Implementation of Green Human Resource (Green HR) Policies (X5.2) and Women's Roles in Environmental, Social, and Governance (ESG) Initiatives (X5.5), can significantly enhance the factors represented by X4. The implications of these findings highlight the importance of addressing structural barriers through policies and initiatives targeting critical areas. Cultural and policy reforms are essential to creating an environment that supports women's empowerment. Digitalization and access to technology, as well as digital skills for women, are also crucial. A holistic approach that integrates policies for gender awareness training and removing structural barriers across various sectors will create a fairer environment for women's leadership. These strategies are expected to help close the gender gap and empower women to take on leadership roles effectively.